2011
DOI: 10.1063/1.3638709
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure equation of state properties of bismuth oxide

Abstract: The high pressure equation of state response of hot pressed bismuth trioxide (Bi2O3) powder compacts is determined through a series of parallel plate impact gas-gun experiments. Loose powders of Bi2O3 are hot-pressed to an average density of 9.202 g/cm3, corresponding to 96% theoretical maximum density. Shock compaction of the compacts to pressures between 4-17 GPa reveal full consolidation occurring at pressures above ∼ 8 GPa. Using the experimentally determined Hugoniot of the 96% dense compact, calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…We report the EOS of the monoclinic phase in both synthetic and mineral samples and compare it with that recently obtained [16] and with our theoretical calculations. The purpose of our study is to understand the structural behavior of -Bi 2 O 3 at high pressures in order to compare it with that of other V-group sesquioxides, like …”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…We report the EOS of the monoclinic phase in both synthetic and mineral samples and compare it with that recently obtained [16] and with our theoretical calculations. The purpose of our study is to understand the structural behavior of -Bi 2 O 3 at high pressures in order to compare it with that of other V-group sesquioxides, like …”
Section: Introductionsupporting
confidence: 55%
“…The equation of state of both HP and HPC phases also were determined [12].However, scarce information is known about -Bi 2 O 3 at high pressures despite its industrial interest. Only a high-pressure Raman study of -Bi 2 O 3 proposed its amorphisation above 20 GPa [15], and the equation of state (EOS) of synthetic -Bi 2 O 3 was recently studied using shock waves [16].…”
Section: Introductionmentioning
confidence: 99%
“…The structural, vibrational, optical, electric and magnetic properties of -Bi 2 O 3 have been studied under different conditions of temperature or pressure [1,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. These studies report that this material has unusual magnetic and electrical properties such as the existence of internal magnetic fields and a longitudinal magnetoelectric effect [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These studies report that this material has unusual magnetic and electrical properties such as the existence of internal magnetic fields and a longitudinal magnetoelectric effect [9,10]. In addition, shock compression experiments have demonstrated that bismite can be used as thermite mixtures for high pressure (HP) applications [8]. In this context, powder X-ray diffraction and Raman scattering experiments have shown that -Bi 2 O 3 undergoes an amorphization at HP between 15 and 20 GPa depending on the hydrostatic conditions [16,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…High-pressure studies of metal oxides have been given continuous attention leading to discoveries of unusual crystal and electronic structures and dielectric, magnetic and elastic properties not observed at ambient conditions [1][2][3][4][5][6][7][8][9][10][11][12]. Among these substances, the high-pressure form of magnetite (h-Fe 3 O 4 ), described as orthorhombic CaTi 2 O 4 -type structure [13,14], is an important counterpart to the face-centered cubic magnetite (fcc-Fe 3 O 4 ) observed at ambient pressure [15] and above Verwey metalinsulator phase transition (121 K) [16].…”
Section: Introductionmentioning
confidence: 99%